Phase Cyclical Process Requirements for the Development of Embedded Systems - Miyashiro, Magda A. Silvério; Ferreira, Maurício G. V. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Continuously Software Engineering seeks to increase the quality of all kinds of software products, however these different types have different characteristics that need to be observed also in a different way. Currently, the major concern is with the quality of Embedded Computing Systems, as they are a classification of software that are strongly present in our daily lives and often without notice. The greatest feature of such systems is the ability to perform extremely important tasks with little computational resource. In general, such systems have restrictions on development and operation, they require specific requirements. To ensure its functioning in its development, we need to use processes with defined procedures to identify these features. This article presents part of a study being carried out to develop a process framework covering all phases of the development process of embedded systems, organized into phases, activities and document templates that induce developers to carry out the good practices suggested by quality models. It is understood by development, all activities related either to new components or reuse.